Endoscopic Band Ligation for Treatment of Bleeding Internal Hemorrhoids in Primary Referral Hospital - Zein, Ahmad Fariz Malvi Zamzam; Luthfi, Ahmad Ichwan; Pratiwi, Lusi; Adi, Galang Prasetyo (The Indonesian Society for Digestive Endoscopy, 2024)
Aim: This study aims to evaluate the efficacy and safety of endoscopic band ligation (EBL) for bleeding grade III internal hemorrhoids in an evidence-based case report.Method: A search was conducted on PubMed and Cochrane databases based on clinical query, with keywords